Conducting research interviews with bereaved family carers: When do we ask? - Bentley, B.; O'Connor, Moira (Mary Ann Liebert Inc., 2015)
© Mary Ann Liebert, Inc. 2015. Background: Interviews with bereaved family carers to examine the end-of-life experience of the deceased are important tools for palliative care researchers, but the ethics of approaching the bereaved when they are grieving and vulnerable is often debated. Objective: The aim of this study was to explore the insights of bereaved family carers about the most appropriate time to be involved in a research interview about the end of life and death of their family member. Methods: This qualitative study used a social constructionist framework. Twenty-two bereaved family carers of people with motor neurone disease (MND) and cancer were interviewed in Western Australia. Results: Most family carers (86%) feel comfortable being interviewed about the death of their family member within the first 5 months of bereavement, with 43% reporting they could be interviewed within weeks after death. Family carers reported that recall would be better earlier in bereavement and felt it may be helpful to them to talk about their experiences earlier. They said bereaved people should be allowed to decide for themselves when to be involved in an interview. Conclusions: These findings indicate that interviews with the bereaved may be most fruitful for researchers and beneficial to family carers when they are allowed to make the choice about timing for themselves, beginning weeks after the death of their family member.